Digital Tax for Developing Asia Countries: a Systematic Literature Review - Tirta Mustika Yudhistira; Muhammad Rizky Ramadhan; Dara Ayu Lestari; Muhammad Zilal Hamzah; Sumiyarti Sumiyarti (Penerbit Goodwood, 2026)
Purpose: This study examines digital taxation within the global economy, analyzes the role of Pillar One by OECD-G20 in addressing the limitations of traditional international tax rules, and assesses the potential impact of digital tax reform on developing countries, especially those in Asia. Methodology: This study employs a Systematic Literature Review (SLR) using the PRISMA methodology. Data were collected from 30 peer-reviewed journal articles indexed in Scopus, published between 2020 and 2025. These articles were selected through keyword-based searches and analyzed using bibliometric techniques with the VOSviewer application to identify research trends and thematic patterns in the digital taxation literature. Results/Findings: The findings reveal that digital taxation has become a crucial policy instrument for overcoming challenges posed by the digital economy, particularly the difficulty faced by market countries in taxing foreign digital companies. Conclusions: This study finds that OECD-G20 Pillar One addresses the limitations of traditional international tax rules by redefining the nexus and reallocating taxing rights toward market jurisdictions. The results further indicate that digital tax reform has significant potential to expand the tax base and strengthen fiscal capacity in developing Asian countries Limitations: This study is limited by its reliance on Scopus-indexed journal articles, potentially excluding relevant literature from other databases or grey sources. Additionally, the literature-based and bibliometric approaches do not allow for the direct measurement of the fiscal impact of digital tax reforms. Contributions: This study contributes to the literature by offering a systematic overview of digital taxation and providing policy-relevant insights for developing economies.